Preface and dedication as genres in sixteenth-century England - Ruokkeinen, Sirkku Inkeri; Mäkinen, Susanna (Uusfilologinen yhdistys, 2026)
In this essay, we study the structure and content of the sixteenth century English preface and dedication. We conduct a move analysis of a corpus of 115,000 words consisting of 113 paratexts, namely prefaces and dedications, collected from the Early English Books Online. Relying on previous scholarship on genre, paratextuality, and book history, we interrogate the closely linked but separate genres of early modern English preface and dedication and conclude that the projected audiences, changes in production methods and the growth of the market contributed to the development of an English Renaissance dedication and preface, and what made them distinct from the previously established continental prefacing models.